The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2010
DOI: 10.1007/s11249-010-9719-9
|View full text |Cite
|
Sign up to set email alerts
|

Friction Properties of Fluorinated Carbon Nanodiscs and Nanocones

Abstract: The tribologic properties of carbon nanodiscs and nanocones and their fluorinated derivatives are investigated and correlated to their structure and chemical composition (atomic fluorine/carbon ratio). Two families of products are studied obtained by fluorination of ill ordered and highly graphitized carbon nanodiscs and nanocones. The studies clearly point out that friction properties of the nanoparticles are strongly dependent on the structure of the initial carbonaceous compounds. Better tribologic behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
(56 reference statements)
1
13
0
Order By: Relevance
“…(1), we obtain L a = 3.9 nm, comparable with previous works [15,16]. AFM measurements performed in a scan window of 350×350 nm 2 on the surface of a nanodisk are shown in Figure 4.…”
Section: Accepted M Manuscriptsupporting
confidence: 88%
See 1 more Smart Citation
“…(1), we obtain L a = 3.9 nm, comparable with previous works [15,16]. AFM measurements performed in a scan window of 350×350 nm 2 on the surface of a nanodisk are shown in Figure 4.…”
Section: Accepted M Manuscriptsupporting
confidence: 88%
“…7 the coherence length L a , which shows the lateral extension of the monocrystalline graphitic domains [14,15]:…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The authors concluded then that the as-synthesized discs can be described as a graphitic core within an envelope of ill organized carbons; The graphitic core (2-5 nm thickness) being first grown up to the final diameter of the nanodiscs, the deposition of amorphous carbon on the initial graphitic core leads to the final thickness. The heat-treatment at 2700 8C induces the graphitization of the ill organized carbon parts with a growth of the graphitic domains parallel to the initial graphitic core (parallel to the disc surfaces) as already demonstrated by AFM measurements [13,22]. This extended graphitic structure may result in the reduction of friction through cleavage between the graphene layers.…”
Section: Tribological Propertiesmentioning
confidence: 59%
“…For the cases of graphitized carbon blacks (m GCBs = 0.12 AE 0.01) and carbon nanofibres (m CNFs = 0.14 AE 0.01), the friction coefficients are close to those obtained for graphite in air (0.10-0.15) whereas m is lower (m CNDs = 0.08 AE 0.01) for the graphitized nanodiscs. This can be attributed to the highly organized structure of CNDs (large graphitic domains) compared to the other nanocarbons [13]. The fluorination process leads to an improvement of the friction properties (decrease of the friction coefficient) for CNFs and GCBs (0.065 < m < 0.085) whereas the friction coefficient recorded in the case of CNDs remains constant whatever the F/C content.…”
Section: Tribological Propertiesmentioning
confidence: 99%
See 1 more Smart Citation